PELATIHAN KONTEN KREATIF DALAM PEMBERDAYAAN UMKM DI KABUPATEN MAROS MELALUI STRATEGI BISNIS DIGITAL - Wahyudi Putera; Desy Rahmawati Anwar; Riska Sucianti; Andi Agusniati; Nisma Iriani; Mahmud, Mahmud; Mattarima, Mattarima (Tahta Media Grup, 2024)
The COVID-19 pandemic and global economic instability, such as the Russia-Ukraine conflict, have had a negative impact on the Indonesian economy, particularly the micro, small and medium enterprise (MSME) sector. This impact is evident for MSMEs in Maros District, which have experienced a decline in sales and difficulty adapting to the changing digital landscape. One of the major problems faced is the low quality of digital marketing content and the lack of understanding in developing effective business strategies. This article discusses the empowerment of MSMEs in Moncogloe District, Maros Regency through creative content, Business Model Canvas (BMC) and digital photography training, as part of an effort to improve the competitiveness of MSMEs in the digital era. The training was designed to help MSMEs overcome marketing challenges by equipping them with practical skills to create more engaging content, map out the right business strategy through BMC and improve product image quality through basic photography techniques. The results of the training showed a significant improvement in participants' ability to execute more effective marketing strategies, increase customer engagement through digital platforms, and strengthen their overall business activities. With better understanding and skills in digital marketing and business strategy, MSME partners are expected to increase their revenue and competitiveness in the market.